2013
DOI: 10.1093/infdis/jit001
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus Type C E2 Protein Inhibits Human Immunodeficiency Virus Type 1 Assembly Through Interference With HIV-1 Gag Plasma Membrane Targeting

Abstract: GB virus type C (GBV-C) is a single-stranded positive-sense RNA virus classified in the Flaviviridae family. Persistent coinfection with GBV-C is associated with lower human immunodeficiency virus type 1 (HIV-1) load, higher CD4(+) T-cell count, and prolonged survival in HIV-1 coinfected patients. The GBV-C envelope glycoprotein E2 has been reported to interfere with HIV-1 entry. In this study, we showed that the expression of GBV-C E2 inhibited HIV-1 Gag assembly and release. Expression of glycosylated GBV-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In another study, patients co‐infected with GBV‐C genotype 2 had higher T‐helper CD4+ cell counts compared to those with genotype 1 [Schwarze‐Zander et al, ]. One possible mechanism underlying this phenomenon may be the interference of the GBV‐C envelope glycoprotein E2 with HIV‐1 cell entry [Xiang et al, ; Timmons et al, ]. Other GBV‐C peptide domains, such as the non‐structural 5A (NS5A) phosphoprotein and non‐structural 3‐serine protease, have also been reported to inhibit HIV‐1 replication [Xiang et al, ; George et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, patients co‐infected with GBV‐C genotype 2 had higher T‐helper CD4+ cell counts compared to those with genotype 1 [Schwarze‐Zander et al, ]. One possible mechanism underlying this phenomenon may be the interference of the GBV‐C envelope glycoprotein E2 with HIV‐1 cell entry [Xiang et al, ; Timmons et al, ]. Other GBV‐C peptide domains, such as the non‐structural 5A (NS5A) phosphoprotein and non‐structural 3‐serine protease, have also been reported to inhibit HIV‐1 replication [Xiang et al, ; George et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the secretory signal peptide of immunoglobulin G (IgG) was fused to the N-terminus of E2 to create a glycosylated E2 expression construct (IgG-E2). We previously showed that the GBV-C envelope glycoprotein E2 (IgG-E2) could inhibit HIV-1 assembly and release by disrupting the targeting of HIV-1 Gag to the plasma membrane [ 17 ]. As the ARF proteins were reported to facilitate Gag-membrane binding [ 26 ], we decided to examine whether the E2 expression has an effect on ARF proteins and mRNA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Since ARF1 is the most abundant, active and best-characterized ARF family protein [reviewed in [ 24 ]], we will focus on studying the interplay between IgG-E2 and ARF1 in this study. The unglycosylated E2 and E2DMID, which had no effect on HIV-1 assembly and release in our prior study [ 17 ], were used as a control in this study. Both IgG-E2 and E2DMID contain an IgG signal peptide at the N-terminus, and the only difference between them is the internal deletion of the membrane interaction domain (MID) region of IgG-E2 in the E2DMID construct.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment, cells were analyzed by either qRT-PCR or Western-blot as described previously [43].…”
Section: Methodsmentioning
confidence: 99%